Response of a self-powered offshore floating support structure with an OWC for powering a LIDAR device. (15th January 2021) - Mathias, Nuno; Marini, Rebeca Nunes; Morais, Tiago; Luís, Pedro; Vaz, Mário; Rosa-Santos, Paulo
Abstract: To give an effective response to the increasing demand to characterise wind availability and intensity for the installation of future offshore wind farms, SPAR buoy OWCs with LIDAR present a clear benefit, due to their stability, mechanical and operational simplicity and lower cost, when compared to wind measuring towers, serving as an alternative to the latter, mainly for deep water. This paper proposes a compromise between a stable SPAR buoy for wind measurements (average speed, gusts, etc.) and a sufficiently capable energy generating OWC device for long-term self-sustainability. Key parameters such as mass distribution and geometry were accounted for, in order to achieve both outcomes. The performance of an oceanic SPAR buoy OWC was analysed numerically and experimentally tested at 1:16 scale, under regular and irregular sea states, in order to quantify its hydrodynamic behaviour and capability to generate electrical energy, using two different PTO configurations. Depending on the sea-states, different PTO configurations result in better performance. For higher significant wave heights, the 39% porosity membrane used as a PTO performed better from a power perspective, whereas for lower significant wave height, the 70% porosity membrane presented better results. Low energy consumption wind measuring equipment may benefit from this application. Highlights: Self-sufficient LIDAR in SPAR buoy with an OWC device. 2 PTO configurations in BEM with lab validation. Successful application of offshore damping estimate for OWC performance.